Descriptions on two new species of the genus Macromotettixoides (Orthoptera: Tetrigidae: Metrodorinae ) from China - Fan, Cheng-Mei; Li, Miao; Mao, Ben-Yong (Zootaxa, 2023)
Two new species Macromotettixoides amplifronta sp. nov. and M. yingjiangensis sp. nov. from Yunnan, are described and illustrated with photographs. An updated key to species of the genus Macromotettixoides is provided.